PELATIHAN BUDIDAYA IKAN MAS DALAM KOLAM TERPAL DENGAN SISTEM RESIRKULASI - Chalvyn Silasa Pakidi; Sendy Lely Merly; Budi Doloksaribu (Musamus Devotion Journal, 2022)
Carp (Cyprinus carpio) is a freshwater fish that is commonly cultivated because carp are large and tame when cultivated. In addition, carp can be bred and have a beautiful colours, moreover tend to famous among local people as a consumption fish, which is also can be used as ornamental fish. Carp can be cultivated in lowland waters to highland areas. In fish farmingm it is important to pay attention to good and clean water quality. Carp can be kept in earthen ponds, rushwater ponds, cages and also tarpaulin ponds. Carp rearing in tarpaulin ponds is usually carried out on narrow land and limited water ability. In there circumstances, it is necesarry to provide water that can support the life of carp to provide good quality of water is to do water recirculation. Resirculation technique is a water recycling technique that has been used. This technique basically performs physical, chemical and biological methods, but which is more environmentally friendly with physical and biological methods, for that in this activity physical and biological methods will be carried out using water filters from sand and aquatic plants. As a result, participants understand how good and correct cultivation techniques are, obtain information bioecology of carp, hatchery techniques, spawning techniques, resirculation techniques including threaten by various diseases and others causes in cultivation carp business. Furthermore, participants also gain more knowledge about what materials and proper equipment they should using and urgently needed to build a cultivation business on limited land and low water flow